2017
DOI: 10.1037/scp0000141
|View full text |Cite
|
Sign up to set email alerts
|

The opiate of the masses: Measuring spiritual bypass and its relationship to spirituality, religion, mindfulness, psychological distress, and personality.

Abstract: This article discusses the development of the Spiritual Bypass Scale-13 (SBS-13). Spiritual bypass is a clinical process of avoiding difficult psychological material using spiritual beliefs, practices, or experiences. A major limitation to the literature on spiritual bypass is that no psychometrically sound measures of the phenomenon exist, thus preventing scholars and clinicians from understanding its causes and treatment implications beyond anecdotal case reports. The SBS-13 was developed using a community s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(91 citation statements)
references
References 25 publications
15
76
0
Order By: Relevance
“…For this purpose, we started by analyzing bivariate correlations to determine relationships between both factors of spiritual bypass to depression, anxiety, stress, Superiority, and preference for solitude. Consistent with previous research (see Fox et al, 2017), results show (see Table 2) Spiritualizing to positively correlate with anxiety, depression, and stress, while Psychological Avoidance negatively correlates to preference for solitude and Superiority. No significant correlation is found between Psychological Avoidance and anxiety, depression and stress or between Spiritualizing with preference for solitude and Superiority.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…For this purpose, we started by analyzing bivariate correlations to determine relationships between both factors of spiritual bypass to depression, anxiety, stress, Superiority, and preference for solitude. Consistent with previous research (see Fox et al, 2017), results show (see Table 2) Spiritualizing to positively correlate with anxiety, depression, and stress, while Psychological Avoidance negatively correlates to preference for solitude and Superiority. No significant correlation is found between Psychological Avoidance and anxiety, depression and stress or between Spiritualizing with preference for solitude and Superiority.…”
Section: Discussionsupporting
confidence: 81%
“…Our first study shows the scale to have a factorial structure of two subscales for this population, as indicated by the CFA. The items on the subscales align with those found on the original version: (a) Psychological Avoidance and (b) Spiritualizing (see Fox et al, 2017). However, we found two major differences between the Brazilian version and the original SBS-13.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…However, what appears at first impression to be authentic spiritual maturity is in fact a way of remaining unopen to the demands of spiritual growth, namely, the willingness to accept both positive and negative experience. Both theory and research have, in fact, concluded that people who consider themselves to be spiritual may be the most prone to spiritual bypass (Cashwell et al, ; Fox, Cashwell, & Picciotto, ; Masters, ). If this is indeed true, it is possible that many people either experience or witness spiritual bypass given that the majority of people nationally and globally report being spiritual, religious, or both (Pew Research Center, , ).…”
mentioning
confidence: 99%